2018
DOI: 10.1039/c8gc02645a
|View full text |Cite
|
Sign up to set email alerts
|

Amide-functionalized heterometallic helicate cages as highly efficient catalysts for CO2 conversion under mild conditions

Abstract: Mimicking nature seems to be one of the smartest strategies to design novel catalysts for CO2 conversion under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…CO 2 is an ideal C1 resource as it is rich, renewable, and nontoxic. However, its stable thermodynamic properties greatly limit its application. , Cycloaddition of CO 2 and epoxides is a 100% atom-economic reaction which forms cyclic carbonates that have found extensive application as battery electrolyte, pharmaceutical/fine chemical intermediates, polymer and engineering plastic syntheses, aprotic polar solvents, etc. Reactions of CO 2 and epoxides may also produce polycarbonates, which may be used as food packagings, adhesives, and optical media . A number of catalysts have been developed to catalyze the cycloaddition reaction, including transition metal (e.g., Cr, , Mn, , Fe, Co, and Zn), main group metal (e.g., Al, Mg, and Ca), rare-earth (RE) metal, and organocatalysts. …”
Section: Introductionmentioning
confidence: 99%
“…CO 2 is an ideal C1 resource as it is rich, renewable, and nontoxic. However, its stable thermodynamic properties greatly limit its application. , Cycloaddition of CO 2 and epoxides is a 100% atom-economic reaction which forms cyclic carbonates that have found extensive application as battery electrolyte, pharmaceutical/fine chemical intermediates, polymer and engineering plastic syntheses, aprotic polar solvents, etc. Reactions of CO 2 and epoxides may also produce polycarbonates, which may be used as food packagings, adhesives, and optical media . A number of catalysts have been developed to catalyze the cycloaddition reaction, including transition metal (e.g., Cr, , Mn, , Fe, Co, and Zn), main group metal (e.g., Al, Mg, and Ca), rare-earth (RE) metal, and organocatalysts. …”
Section: Introductionmentioning
confidence: 99%
“…The catalytic performance of Zr-AZDA is comparable to that of the best homogeneous catalyst (such as NaI • 2H 2 O and Co-Salen), [15,18] and Zr-AZDA also shows higher catalytic activity than most of the reported heterogeneous catalysts (such as Basic-Nano-ZSM-5-Pr-MIM-OH, PIPÀ Bn-Cl, PS-ImHI, MgÀ Al mixed Oxide, MgO nanoparticle, IT-POP-1, CNTammonium salt, MOPÀ Zn-1, CuTrp MOF, Helicate cage, Nu-1000 and Hf-NU-1000). [24,25,[27][28][29]31,36,44,55,64,65] Although the catalytic reaction conditions used in the literatures are versatile, in general the Zr-AZDA catalyst has obvious advantages such as mild reaction conditions, solvent-free at atmospheric pressure (1 atm) and higher catalytic activity.…”
Section: Investigation On the Catalytic Performancementioning
confidence: 99%
“…[54] However, the application of MOPs as Lewis-acid catalysts for CO 2 cycloaddition reaction is rare. [22,55] Recently, a few MOPs that are highly soluble in organic solvents were reported by functionalization with dodecoxyl groups on the framework. [56] The soluble MOPs as homogeneous catalysts would not have the aggregation problem, but the recycling of the MOPs has not been well addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The IR spectrum of 2 confirmed that the structural integrity of 2 was well maintained after catalysis (Figure 2b). The cycle of the catalytic system was successfully repeated seven times with little change in conversion (Figure 2a The recyclability and stability of a catalyst plays an integral role in practical application [24,28,29]. The recycling experiment was carried out by the optimal reaction conditions obtained under the above experiment, i.e., 60 °C and 10 bar of CO2 and 12 h. 1 mol% of the catalyst and propylene oxide were placed in an autoclave and passed through 10 bar of CO2 for 12 h to calculate the yield.…”
Section: Catalytic Activity For Co 2 Fixationmentioning
confidence: 99%